Sex differences in the factors that affect medical lethality in elderly suicide attempters - Kim, HeungKyu; Min, Seongho; Ahn, Joung-Sook; Kim, Hyun; Cha, Yong Sung; Lee, Jinhee; Kim, Min-Hyuk (Frontiers in Psychiatry, 2023)
Objectives: This study aimed to identify sex differences in the factors that affect medical lethality in elderly suicide attempters. Methods: A total of 253 elderly suicide attempters and 351 middle-aged attempters (comparison group) who visited the emergency room at a general hospital were included. The sociodemographic and clinical characteristics of the patients were investigated. The Chi-squared test and logistic regression analysis were performed. And Spearman's correlation coefficient was calculated. Results: In older males, the risk of high lethality was lower when attempting suicide due to the loss of family members (adjusted odds ratio (AOR): 0.08). The risk increased as the intent to die became more certain (some AOR: 11.31, certain AOR: 28.75), and this association became more pronounced with age (rho middle-aged: 0.329; young-old: 0.387; old-old: 0.415). In older females, the risk was lower when employed (AOR: 0.28). The method of suicide attempt also affected lethality (agricultural chemicals AOR: 3.71; psychiatric medication AOR: 0.31). Conclusions: Sex differences in the factors that affect medical lethality were identified among elderly suicide attempters. In particular, medical lethality can be predicted by the degree of suicide intention in older males. These findings will help to establish more efficient preventive strategies with specific targets.